2015
DOI: 10.1002/lary.25230
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department presentation for uncomplicated acute rhinosinusitis is associated with poor access to healthcare

Abstract: Objectives/Hypothesis Uncomplicated acute rhinosinusitis (ARS) is most appropriately managed in an outpatient clinic setting. Some ARS patients present to emergency departments (EDs) for care. We investigates factors associated with ARS presentation to EDs versus outpatient settings. Study Design Cross‐sectional study. Methods A total of 17,122,551 pediatric and adult patient visits from the 2009 and 2010 National Ambulatory Medical Care and National Hospital Ambulatory Medical Care Surveys for ARS were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…We have previously characterized factors associated with ED presentation for uncomplicated ARS and found an association with insurance status . Specifically, Medicaid and self‐pay insurance statuses were associated with ED presentation for uncomplicated ARS, suggesting healthcare access may be one factor driving ED utilization for this disease.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have previously characterized factors associated with ED presentation for uncomplicated ARS and found an association with insurance status . Specifically, Medicaid and self‐pay insurance statuses were associated with ED presentation for uncomplicated ARS, suggesting healthcare access may be one factor driving ED utilization for this disease.…”
Section: Introductionmentioning
confidence: 94%
“…The need for urgent evaluation is rare, and most uncomplicated ARS can be treated conservatively with observation or a brief course of antibiotics. Despite this typically benign nature, approximately 500,000 patients with ARS present to EDs for evaluation annually, leading to a considerable economic impact on healthcare expenditures …”
Section: Introductionmentioning
confidence: 99%
“…Overall, 93.5% of uncomplicated ARS visits were to a PCP, and 6.5% of visits were to the ED. These percentages are comparable to those reported in our prior work, in which 94.2% of visits were to a PCP and 5.8% were to an ED . Seven percent of adult visits versus 4.8% of pediatric visits were to an ED.…”
Section: Resultsmentioning
confidence: 99%
“…Concerns exist regarding problems with access to care and quality of care for not only the uninsured but also patients with Medicaid . We previously have found that for uncomplicated acute rhinosinusitis (ARS)—a common condition with more than 20 million cases annually in the United States—patients with Medicaid or self‐pay insurance status disproportionately are more likely to present to an emergency department (ED) for ARS versus privately insured patients . Children and adults suffering from ARS may seek care at an ED or primary care provider (PCP); in both cases, over 50% of adult and pediatric ARS patients receive an antibiotic independent of insurance status .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that social and racial disparities may negatively influence healthcare decision making in the ED setting . Several studies have now elucidated socioeconomic disparities in otolaryngology ED care, including utilization of computed tomography scans and presentation to the ED for acute rhinosinusitis …”
Section: Introductionmentioning
confidence: 99%